Effectiveness and safety of three NiTi systems in endodontic retreatment of MB1 and MB2 root canals: a micro-CT and CBCT combined analysis - Santos-Junior, Airton Oliveira [UNESP] (2025)
Objective: To evaluate the performance in endodontic retreatment and pericervical dentin preservation using ProDesign Logic (PDL), Reciproc Blue (RB), and WaveOne Gold (WOG) NiTi systems in first (MB1) and second (MB2) mesiobuccal root canals of maxillary molars, using cone-beam computed tomography (CBCT) and micro-computed tomography (micro-CT). Materials and methods: MB1 and MB2 canals were prepared, filled, and randomized into four groups (n = 8). MB1 were retreated using PDL up to file 40/0.05 or RB R40 (40/0.06), while MB2 were retreated using PDL up to file 35/0.05 or WOG (35/0.06). Micro-CT scans were performed before and after retreatment to assess the remaining filling material, canal transportation, and canal centralization. Dentin removal and remaining dentin were measured at four levels below the furcation through CBCT scans analyzed with the e-Vol DX software, with micro-CT serving as the reference standard. Results: RB was more effective than PDL in removing MB1 filling material, while PDL outperformed WOG in the apical third of MB2 (p < 0.05). Overall, CBCT measurements for dentin removal were consistent with micro-CT in MB1 but occasionally underestimated in MB2 (p < 0.05). A significant reduction in MB2 danger zone dentin thickness below 0.5 mm was observed after retreatment (p < 0.05). Conclusions: RB was more effective in retreating MB1, while PDL was more efficient in the apical third of MB2. A substantial decrease in dentin thickness in the MB2 danger zone was noted after retreatment, regardless of the NiTi system or imaging modality used. Overall, CBCT scans provided consistent assessments of dentin. Clinical relevance: Selecting appropriate NiTi systems minimizes dentin removal in MB1 and MB2 danger zones, reducing the risk of perforation in the furcation area. CBCT reliably assesses dentin thickness, aiding clinical decisions and improving endodontic retreatment outcomes.